MENCIPTAKAN STARTUP YANG SUSTAINABLE DAN PROFITABLE DI LINGKUNGAN ENTREPRENEUR UNIVERSITY - Yuni Mutia Astiti; Martani Huseini (Politeknik Negeri Bengkalis, 2019)
This article is conducted on a simple question: how can a university create a sustainable and profitable startup? At present it is very difficult to predict changes in the future because even if conducting market research the results change rapidly. This is feared to have an impact on the existence of startups that are present in Indonesia so that they are unable to fulfill the consumers' desires for the products or services created by the startup. A traditional management has not been able to overcome uncertainty in the future. Therefore, the concept of an entrepreneur university is needed and also a more comprehensive method to deal with it. The purpose of this research is to build a startup at an entrepreneur university environment. The output of this research is in the form of a table of operationalisation of concepts that are expected to be used to help the success of startups created through an entrepreneur university.